Metacognition in Language Learning and Teaching - Haukås, Åsta; Bjørke, Camilla; Dypedahl, Magne (Routledge Studies in Applied Linguistics, 2018)
The Open Access version of this book, available at https://www.taylorfrancis.com/books/e/9781351049139, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license. This volume offers an exhaustive look at the latest research on metacognition in language learning and teaching. While other works have explored certain notions of metacognition in language learning and teaching, this book, divided into theoretical and empirical chapters, looks at metacognition from a variety of perspectives, including metalinguistic and multilingual awareness, and language learning and teaching in L2 and L3 settings, and explores a range of studies from around the world. This allows the volume to highlight a diverse set of methodological approaches, including blogging, screen recording software, automatic translation programs, language corpora, classroom interventions, and interviews, and subsequently, to demonstrate the value of metacognition research and how insights from such findings can contribute to a greater understanding of language learning and language teaching processes more generally. This innovative collection is an essential resource for students and scholars in language teaching pedagogy, and applied linguistics.